Cetaceans using the marine protected area of "Parque Estadual Marinho da Laje de Santos", Southeastern Brazil - Marcos Cesar de Oliveira Santos (10477346); Giovanna Corrêa e Figueiredo (10476766); Marie-Francoise Van Bressem (10477349) (2017)
Abstract The aim of this study was to evaluate the presence of cetaceans in the waters surrounding the Marine Protected Area (MPA) known as “Parque Estadual Marinho da Laje de Santos (PEMLS)”, placed in coastal waters at the southeastern coast of Brazil. Boat-based surveys were conducted once a month from June 2013 to June 2015. A specific transect was followed to cover the area of the quoted MPA, as well as its borders. A total of 24 boat-surveys rendered 18 sightings of cetacean groups of the following species: Atlantic spotted dolphin (Stenella frontalis) (12), rough-toothed dolphin (Steno bredanensis) (2), common dolphin (Delphinus delphis) (1), Bryde’s whale (Balaenoptera edeni) (2) and common minke whale (Balaenoptera acutorostrata) (1). Sightings of S. frontalis, the commonest sighted species, was positively correlated with water depth (Mantel test; r = 0.8072; p < 0.05). Photoidentified individuals moved back and forth to inner and outer areas of the MPA, remaining in the area throughout the 2-year survey. “Paisley” cutaneous marks of unknown origin were reported in two common dolphins for the first time in local waters. As the PEMLS has been used as an important spot for SCUBA divers, it is recommended that cetacean sightings could still be gathered in a future partnership, as well as using the acoustics tool to detect their presence when researchers are not in the field.